Pengaruh Profesionalisme Guru Terhadap Kinerja Guru di Gugus IV Srikandi Kecamatan Plumpang Kabupaten Tuban Tahun Ajaran 2025/2026 - Rumiyati Rumiyati; Taufiq Harris; Faizin Faizin (LPPPI Publishing, 2026)
the quality of education means improving the quality of teachers. A professional teacher is someone who is well educated and trained, and has rich experience in its sector. Teacher Professional Education (PPG) is a strategic program designed to develop and strengthen a teacher's professional competency. In other words, it can be stated that if teacher professionalism is high, teacher performance will increase. The method used in this research is quantitative. The variables in this study consist of one independent variable and one dependent variable. The dependent variable (y) is teacher performance and the independent variable (x1) is teacher professionalism. The population to be studied in this research is elementary school teachers in Cluster IV Srikandi, Plumpang District, Tuban Regency with a total of 50 people/respondents. The method that will be used in this research is the questionnaire method. The research results obtained the following data: 31 teachers or 62% of teachers in Cluster V Srikandi, Plumpang District, Tuban Regency in the 2025/2026 Academic Year had teacher professionalism scores above the mean, and the remaining 38% or 19 teachers were below the average. For the teacher performance variable, the final results showed that 33 teachers or 56.0% had scores above the average, while 27 teachers or 44% had scores below the average. Based on the findings of this study, it can be concluded that there is a positive and significant influence between teacher professionalism and teacher performance in Cluster V Srikandi, Plumpang District, Tuban Regency in the 2025/2026 Academic Year.